Coupling Relationship between Multistage Fluid Activity and Reservoir Abnormally High-Porosity Zones in the Songtao–Baodao Region, Qiongdongnan Basin. (17th May 2021) - Chen, Xu; Wang, Yao; Su, Ao
Abstract : An abnormally high-porosity zone (AHPZ) is beneficial for petroleum exploration, especially for the deep tight reservoirs in a petroliferous basin. Because of lacking effective research methods, it is hard to analyze the formation process of AHPZs in different geological periods. From the perspective of the diagenetic fluid type and activity history, geochemical characteristics and fluid inclusions of diagenetic minerals were utilized to reconstruct the diagenetic fluid type and dynamic evolution. The ultimate goal is to study the genetic process of AHPZs in the Songtao–Baodao region of the Qiongdongnan basin, South China Sea. It was found that there are three sections of AHPZs at different burial depths, which are generally favorable for high-quality reservoirs. Moreover, it can be concluded that the AHPZs are closely related to multiple actions of various diagenetic fluids. The meteoric waters, organic acid, and thermal fluids facilitated the enlargement of porosity by dissolving minerals to form secondary pore spaces. The hydrocarbon fluids have positive effects on the preservation of pores by preventing cement from filling the pore space.